A descriptive study of differential stuck pipe problem in Nahr Umr oil field: principles and treatments - Alhisnawy, Karrar Talib; A. Alrazzaq, Ayad A. Alhaleem; Emtair, Waleed M. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Differential-pressure pipe sticking is one of the main problems that occurs during drilling operations, leading to an increase in the non-productive time (NPT). To address this problem, the industry uses a range of spotting fluids to enable the recovery of a differentially stuck pipe effectively. Thus, any delay in solving this problem can turn into a difficult rescue operation that can eventually lead to the abandonment of the well in extreme conditions. Therefore, it is crucial to choose the appropriate spotting fluid that is suitable for the specific mud composition, as using an unsuitable spotting fluid may result in dangerous conditions. Additionally, other factors can further complicate the process of freeing a stuck pipe. Therefore, for prevention, remediation, and enhancing the recovery of stuck pipes, it is important to understand the root causes of the pipe sticking issue, the conditions that lead to it, and the operational mechanisms of various spotted fluids and their application areas. This paper studies the challenges of pipe sticking during drilling operations, particularly emphasizing differential pipe sticking, and the role of spotting fluids in releasing pipe sticking. It discusses the testing and evaluation methods used to choose appropriate spotting fluids while rejecting the inferior options, highlighting the benefits and disadvantages. This study, which was conducted at Well NR-A in the Nahr Umr field in southeastern Iraq, aims to address the problem of differential stuck pipes. By employing a stuck pipe list check table, the mechanism of this problem was diagnosed, resulting in a thorough analysis of the causes of differential stuck pipe and subsequent steps necessary to release the stuck pipe. Finally, recommendations are presented to improve testing and evaluation methods, overcoming the limitations of conventional methods.